Relationships between Duration of Breastfeeding, Child Nutritional Status, and Development - Jamaluddin, Sri Rezki Wahdania; Faradilah, Andi; Fitriani, Rini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Breast milk is one of the factors that can affect growth and development. WHO is promoted exclusive breastfeeding and also encourages mother to raise breastfeeding until the children reach 2 year of age. This study was aimed to examine the relationships between the duration of breastfeeding, child nutritional status and development. Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted in three health centers, in Makassar, South Sulawesi, Indonesia, from December 2019 to January 2020. A total of 200 mothers with children aged 1-3 years old were selected by purposive sampling. The dependent variables were child nutritional status and child development. The independent variable was duration of breastfeeding. Child development was measured using developmental pre-screening questionnaire. The other variables were collected by questionnaire. The relationships between variables were analyzed by Pearson correlation. Results: Duration of breastfeeding was not associated with child nutritional status (r= -0.01; p= 0.970). Duration of breastfeeding increased child development, but it was statistically not significant (r= 0.04; p= 0.550). Conclusion: Duration of breastfeeding is not associated with child nutritional status. It increases child development, but it is statistically not significant.